A wide neighborhood infeasible-interior-point method with arc-search for -SCLCPs. (4th March 2018) - Shahraki, M. Sayadi; Mansouri, H.; Zangiabadi, M.
Abstract: In this paper, we propose an arc-search infeasible-interior-point method based on the wide neighbourhood for linear complementarity problems over symmetric cones with the Cartesian -property ( -SCLCP). The algorithm searches the optimizers along the ellipses that approximate the central path. Moreover, we derive the complexity bound of the algorithm which coincides with the currently best known theoretical complexity bounds for the short step path-following algorithm. Some numerical results are provided to demonstrate the computational performance of the proposed algorithm.